Correcting course: the emission reduction potential of international cooperative initiatives. (7th February 2021) - Lui, Swithin; Kuramochi, Takeshi; Smit, Sybrig; Roelfsema, Mark; Hsu, Angel; Weinfurter, Amy; Chan, Sander; Hale, Thomas; Fekete, Hanna; Lütkehermöller, Katharina; Jose de Villafranca Casas, Maria; Nascimento, Leonardo; et al.
ABSTRACT: This article quantifies the aggregate potential of greenhouse gas (GHG) emissions reductions in 2030 from the assumed full implementation of major international cooperative initiatives (ICIs). To this end, a methodology is proposed to aggregate emission reduction goals of the most significant and potentially impactful global initiatives. We identified the extent to which reductions are additional to national policies, assuming these actions do not displace climate actions elsewhere, and accounted for overlap ranges between the ICIs. The analysis was conducted for 17 initiatives, selected from an original list of over 300 with a series of testing criteria, across eight sectors and ten major emitting economies. These initiatives include cities, regions, businesses, and other subnational and non-state actors, cooperating with each other and sometimes working in partnership with national governments or other international organizations. Our analysis shows that the combined achievement of initiatives' reduction goals could reduce global emissions in 2030 by 18–21 GtCO2 e/year in addition to current national policies (total of 60–63 GtCO2 e/year), down to 39–44 GtCO2 e/year. If delivered fully, reductions from these 17 initiatives would help move the global emissions trajectory within the range of a 2°C-consistent emission pathway by 2030, although a significant gap would remain to reduce emissions to a 1.5°C-consistent pathway. Key policy insights We propose a transparent and robust methodology to aggregate GHG mitigation potential of ICIs, accounting for overlaps between ICIs. If major initiatives meet their goals and do not change the course of other existing climate actions, they could make large contributions by 2030 towards global efforts to stay within the range of a below 2°C-consistent emission pathway by 2030. The full suite of existing initiatives beyond those in this analysis could further increase ambition towards achieving the Paris Agreement's temperature goals. Cities and regions, businesses and forestry initiatives account for significantly more than half of all possible emission reductions from ICIs; implementation of their goals should be a key policy focus.